Mechanical recanalization in ischemic anterior circulation stroke within an 8-hour time window: a real-world experience - Krajíčková, Dagmar; Krajina, Antonín; Herzig, Roman; Lojík, Miroslav; Chovanec, Vendelín; Raupach, Jan; Vítková, Eva; Waishaupt, Jan; Vyšata, Oldřich; Vališ, Martin (Diagnostic and interventional radiology (Ankara, Turkey), 2017)
PURPOSE: We aimed to assess the safety and effectiveness of mechanical recanalization in patients with ischemic stroke in the anterior circulation within 8 h since symptoms onset and with unknown onset time. We compared time intervals <6 h vs. 6-8 h/unknown onset time, as only limited data are available for a time window beyond 6 h. METHODS: Our cohort included 110 consecutive patients (44 males; mean age, 73.0±11.5 years) with ischemic stroke in the anterior circulation due to the acute occlusion of a large intracranial artery who underwent mechanical recanalization within an 8-hour time window or with unknown onset time. All patients underwent unenhanced computed tomography (CT) of the brain, CT angiography of the cervical and intracranial arteries and digital subtraction angiography. Perfusion CT was performed in patients beyond a 6-hour time window/with unknown onset time. We collected the following data: baseline characteristics, presence of risk factors, neurologic deficit at the time of treatment, time to therapy, recanalization rate, and 3-month clinical outcome. Successful recanalization was defined as Thrombolysis in Cerebral Infarction score of 2b/3 and good clinical outcome as modified Rankin scale value of 0-2 points. RESULTS: Successful recanalization was achieved in 82 patients (74.5%): in 61 patients treated within 6 h (73.5%), 7 patients treated within 6-8 h (63.6%), and 13 patients with unknown onset time (81.3%). Good 3-month clinical outcome was achieved in 61 patients (55.5%): in 46 patients treated within 6 h (55.4%), 5 patients treated within 6-8 h (45.5%), and 10 patients with unknown onset time (62.5%). Recanalization success or clinical outcome were not significantly different between patients treated at different time windows. CONCLUSION: Our data confirms the safety and effectiveness of mechanical recanalization performed in carefully selected patients with ischemic stroke in the anterior circulation within 8 h of stroke onset or with unknown onset time in everyday practice.
Keywords: senioři; Stroke; senioři nad 80 let; Mechanical Thrombolysis; Brain Ischemia; Retrospective Studies; Tomography, X-Ray Computed; Time Factors; výsledek terapie; digitální subtrakční angiografie; Middle Aged; mužské pohlaví; Adult; cévní mozková příhoda; Aged, 80 and over; ženské pohlaví; retrospektivní studie; Humans; mechanická trombolýza; časové faktory; lidé středního věku; Angiography, Digital Subtraction; dospělí; ischemie mozku; počítačová rentgenová tomografie; Aged; Female; Treatment Outcome; lidé; Male